Penerapan Strategi Pembelajaran Kooperatif Tipe Think Pair and Share Untuk Meningkatkan Hasil Belajar Mata Pelajaran TEMATIK siswa kelas IV Di MI Darussalam Pikatan Wonodadi Blitar Tahun Ajaran 2019/2020 - Khoiruzzaim Kurniawan (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
Tematik lessons require a real understanding of various situations in the surrounding environment or society. For teachers, understanding the nature of Tematik certainly has a major contribution to make the Tematic learning process more meaningful. Seeing the presentation of the problems that occurred at MI Darussalam Pikatan, for this reason the researchers tried to conduct a classroom action research entitled "Application of Think Pair and Share Type Cooperative Learning Strategies to Improve Learning Outcomes for Fourth Grade Tematik Subjects at MI Darussalam Pikatan Wonodadi Blitar in the 2019 Academic Year /2020” to prove that the think pair and share (TPS) type of cooperative learning strategy can improve students' understanding of Tematic concepts and also achieve learning instructional goals. After the second cycle, the final test results obtained the average score of students was 84.48. From the results of the final test of the second cycle, student learning outcomes have increased when compared to the results of the final test of the first cycle, which is 71.36. From the formative test data II, it is known that 29 students have obtained a score of 75 and 4 students have not met the minimum completeness criteria, so the percentage of learning completeness in cycle II is 87.88%, which means that the percentage of student learning mastery has met the predetermined completeness criteria, namely 75%. Learning strategies play an important role in teaching and learning activities. The application of learning strategies that are in accordance with the curriculum and student characteristics can make students active in participating in learning activities. So that it can improve the quality of learning